Soil mechanics fundamentals - Ishibashi, Isao; Hazarika, Hemanta (Boca Raton, Florida CRC Press, 2011)
"Comprehensive and introductory, this textbook covers all basic fundamental concepts of soil mechanics. It delineates how soil behaves, why it behaves that way, and the engineering significance of such behavior. The text clearly explains the various behaviors of soils based on mathematics, physics, and chemistry in simple but comprehensive ways. The authors include essential engineering equations to emphasize the importance of fundamentals, and 180 problems and solutions to aid with application. An instructor's guide, solutions manual, and PowerPoint presentation are available upon qualifying course adoption"-- Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Soil mechanics